2007
DOI: 10.1007/s00122-007-0575-4
|View full text |Cite
|
Sign up to set email alerts
|

Using genotype × nitrogen interaction variables to evaluate the QTL involved in wheat tolerance to nitrogen constraints

Abstract: Lower market prices and environmental concerns now orientate wheat (Triticum aestivum L.) breeding programs towards low input agricultural practices, and more particularly low nitrogen (N) input management. Such programs require knowledge of the genetic determination of plant reaction to N deficiency. Our aim was to characterize the genetic basis of N use efficiency and genotype x N interactions. The detection of QTL for grain yield, grain protein yield and their components was performed on a mapping populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(91 citation statements)
references
References 52 publications
8
81
1
1
Order By: Relevance
“…Dispersion of genes affecting GY across the wheat genome appears to be a characteristic feature (Laperche et al 2007) that was also observed in this study (Table 6). In this study, 213 DArT markers (or 88% of the mapped markers) were significantly associated with GY.…”
Section: Discussionsupporting
confidence: 84%
“…Dispersion of genes affecting GY across the wheat genome appears to be a characteristic feature (Laperche et al 2007) that was also observed in this study (Table 6). In this study, 213 DArT markers (or 88% of the mapped markers) were significantly associated with GY.…”
Section: Discussionsupporting
confidence: 84%
“…They also noted that the traits for which phenotypic and genotypic correlations were most similar for traits that belonged to the same functionally and/or developmentally related set that they described as being ''a higher degree of genetic and phenotypic character integration.'' The important effect of flowering time has been observed in phenotypic correlations reported in other NUE studies (Bogard et al 2011a;Laperche et al 2007;Cormier et al 2013). The magnitude of the genotypic correlations of FLO and HT with NUE traits in our study were much greater than the magnitude of phenotypic correlations reported previously.…”
Section: Genotypic Correlations Among Traitscontrasting
confidence: 52%
“…QTL analyses to identify genomic regions associated with NUE have been conducted using both biparental recombinant inbred and doubled haploid populations from Asian and European germplasm in both seedling and full-season experiments Guo et al 2012;Sun et al 2013;Xu et al 2014;Laperche et al 2006Laperche et al , 2007Laperche et al , 2008Zheng et al 2010;Fontaine et al 2009;Habash et al 2007;Garcia-Suarez et al 2010;Bogard et al 2011bBogard et al , 2013. Association mapping (Bordes et al 2013;Cormier et al 2014) approaches also have been applied to NUE traits.…”
Section: Introductionmentioning
confidence: 99%
“…This implies that the proposal of Martre et al (2007) to search for genotypes able to translocate larger amounts of N to grains without reducing plant biomass and photosynthetic capacity under N shortage has become particularly challenging for local breeders. Nevertheless, a further improvement of grain protein content under N-limited conditions without substantial depressions in yielding capacity seems to be possible in bread wheat, as suggested by Laperche et al (2007). In their recent study, at least some genome regions responsible for wheat performance and protein content (e.g.…”
Section: Variation Of Charactersmentioning
confidence: 91%
“…Moreover, both processes-N uptake and N utilization-appear to be governed by different genetic factors (Hirel et al 2001;Gallais and Hirel 2004;Good et al 2004). For instance, results of extensive molecular studies on wheat and maize Gallais 2000, 2001;Quarrie et al 2005;Habash et al 2007;Laperche et al 2007) revealed that different sets of genes (QTL regions) controlled various components of the two major measures of N efficiency, and that expression of the genes (loci) was considerably dependent upon soil N status. Hence, the appearance of the above-mentioned negative relationship between NUpE and NUtE in the examined hybrids and their parents may be a genetic quandary.…”
Section: Combining Ability Effectsmentioning
confidence: 99%